PENGARUH FINANCIAL TECHNOLOGY DAN LIFESTYLE DIGITAL TERHADAP MINAT INVESTASI PADA MAHASISWA PENDIDIKAN EKONOMI UNIVERSITAS SRIWIJAYA - Deska Aulia, Rachel; Deskoni (Global Action and Education for Society, 2026)
The rapid development of digital technology has driven changes in students’ financial behavior, including their interest in investing. This study aims to examine: (1) the effect of financial technology on investment interest among Economics Education students at Sriwijaya University, (2) the effect of digital lifestyle on investment interest among Economics Education students at Sriwijaya University, and (3) the simultaneous effect of financial technology and digital lifestyle on students’ investment interest. This research employed a quantitative approach with a population of 195 students divided by cohort from 2022-2025. The sample was obtained using the Proportional Random Sampling technique to ensure proportional representation from each cohort. The research instrument used was a questionnaire, and the data analysis included normality, linearity, multicollinearity, and heteroscedasticity tests. The results show that: (1) financial technology has a positive and significant effect on investment interest with a value of t_count = 13.026 > t_table= 1.975 and a coefficient of determination of 46.79%; (2) digital lifestyle has a positive and significant effect on investment interest with a value of t_count= 10.259 > t_table= 1.975 and a coefficient of determination of 35.29%; and (3) financial technology and digital lifestyle simultaneously have a significant effect on students’ investment interest with a value of F_count= 95.86 > F_(table )= 4.02 and a coefficient of determination of 49.96%. These findings indicate that the use of financial technology and the adoption of a digital lifestyle substantially influence students investment interest. Therefore, students are encouraged to utilize technology wisely and develop digital habits that support rational investment decision-making.